2022
DOI: 10.3390/bacteria1030012
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Characterization of Lactiplantibacillus plantarum Strains Possessing Differential Antiviral Immunomodulatory Activities

Abstract: Lactiplantibacillus plantarum strains are used in the food industry for their probiotic properties. Some of these bacteria have immunomodulatory effects on the host and are able to improve resistance against different pathogens, including viruses. However, to date, the bacterial genes involved in the immunomodulatory effect are not known. In this work, the complete genomes of L. plantarum MPL16, CRL1506, CRL681 and TL2766 were used to perform comparative genomics with the aim of identifying the genes involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 76 publications
0
12
0
Order By: Relevance
“…It was reported that surface-exposed proteins play key roles in the interactions of lactobacilli with their environments [ 27 , 28 ]. Therefore, we first evaluated the genes coding surface-exposed and secreted proteins in L. plantarum LOC1 and compared them with CRL1506 and WCSF1 strains ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It was reported that surface-exposed proteins play key roles in the interactions of lactobacilli with their environments [ 27 , 28 ]. Therefore, we first evaluated the genes coding surface-exposed and secreted proteins in L. plantarum LOC1 and compared them with CRL1506 and WCSF1 strains ( Figure 9 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we first evaluated the genes coding surface-exposed and secreted proteins in L. plantarum LOC1 and compared them with CRL1506 and WCSF1 strains ( Figure 9 ). The extracellular proteins in the LOC1 strain were studied by in silico analysis considering the subcellular location (surface-expressed or secreted), the secretory mechanism and the anchorage type, following the guidelines recently described by our group [ 28 ]. Notable differences were detected between L. plantarum LOC1, CRL1506 and WCSF1 when analyzing the 304 genes for extracellular proteins.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations